EVOLUTION OF THE PALEO-ASIAN OCEAN (ALTAI-SAYAN REGION, CENTRAL ASIA) AND COLLISION OF POSSIBLE GONDWANA-DERIVED TERRANES WITH THE SOUTHERN MARGINAL PART OF THE SIBERIAN CONTINENT - Buslov M.M.; Saphonova I.Yu.; Semakov N.N.; Smirnova L.V.; Kazansky A.Yu.; Watanabe T.; Obut O.T.; Fujiwara Y.; Iwata K.; Sugai Y. (My University, 2001)
The paper reviews and integrates new results on the evolution of the Paleo-Asian Ocean and its related geodynamics and geology of Altai-Sayan Region (ASR) in Central Asia. A revised terrane classification based on Vendian-Cambrian geodynamic units and evolution of terranes is described. Reactivated suture zones along the terrane boundaries are proposed. The obtained data suggest the important role of strike-slip deformations in the formation of mosaic-block structure of Central Asia. Those complicated and multi-stage deformations resulted from the Late Devonian-Early Carboniferous collision of Gondwana-derived terranes. The deformations reached their peak in the Late Carboniferous-Permian due to the collision of the Kazakhstan and Siberian continents. A system of sinistral strike-slip faults formed ASR along the margin of the Siberian continent as a result of the Late Carboniferous-Permian collision. The intrusion of granites occurred in East Kazakhstan and northwestern Gorny Altai in the Late Carboniferous and Permian. This resulted in the formation of the Northern Eurasia continent. Geodynamic evolution of the Paleo-Asian ocean and paleotectonics of ASR allow to recognize in the region the following five geodynamic stages: Vendian-Early Cambrian, Early Ordovician, Early-Middle Devonian, Late-Devonian-Early Carboniferous and Late Carboniferous-Early Permian times.
Keywords: Gondwana-derived terranes; Paleo-Asian ocean; terranes; reactivated zones; collision; Altai−Sayan Region